ANDROID BASED 7 SUMMIT SEMBALUN E-TICKET APPLICATION - Elpin Hendriawan; Lalu Puji Indra Kharisma; Wahyu Ramadhan; Ruly Hajar Fauziah (Universitas Islam Negeri Mataram, 2024)
Sembalun Village, as one of the villages that already has infrastructure in the tourism sector, hopes to take advantage of developments in information technology for use in tourism services in the village. Sembalun Village, Sembalun District, East Lombok Regency has many tourist attractions, one of which is the 7 Summit Sembalun. According to ticket sales data for 2022, it is known that public interest is increasing over time, so an application is needed to manage ticket sales. E-ticket applications can help in this business sector by reducing transaction times faster, summarizing documents easily, providing detailed information, and minimizing errors when inputting data. The current ticket sales system for the 7 Summit Sembalun still uses the old or manual method as with conventional ticket sales. The method used in this research is the waterfall method. The waterfall method is a methodology for designing and building software systems; namely, the design process gradually flows downwards (similar to a waterfall). Based on the discussion explained in the previous chapters, through unit testing, it can be concluded that the